Pension investments in employer stock - William E. Even; David A. Macpherson (Institute for the Study of Labor (IZA), 2006)
This study examines the consequences of a pension fund investing in the stock of the sponsoring firm. Using a merger of data on pension asset holdings from IRS Form 5500 filings and financial data on the company's stock from CRSP, two broad questions are addressed: First, what factors influence the extent of a pension fund's investments in the employer's stock? Second, when a pension invests in the employer's stock, how much is lost as a result of poor diversification? The empirical results suggest that investments in employer stock are responsive to non-diversification costs, tax consequences, and employee ability to diversify the risk. There is also evidence that employers and employees weight these factors differentially in their decision of how much employer stock to include in the pension. Using actual return data on pension plans, we also find that concentrated investments in employer stock substantially reduce risk-adjusted return performance.
urn:nbn:de:101:1-20090406216
Keywords: 330